Low-power analog circuit design for AIoT sensors - Zhao, Pengju (Nanyang Technological University, 2024)
Artificial intelligence of things(AIoT) is performing an increasingly important role in digital world. ADC is the connection unit of digital and analog world. While ADC consists of quantities of comparators, the design of low power always-on comparator is required for AIoT sensors deployment.